ON FUNCTIONAL GENERALIZATION OF OSTROWSKI INEQUALITY FOR CONFORMABLE FRACTIONAL INTEGRALS - Tunc, T; Budak, H; Sarikaya, M.Z (TWMS journal of applied and engineering mathematics, 2018)
In this study, we establish a generalized Ostrowski type integral inequality for conformable fractional integrals. We also give some applications for p-norms and exponential.Keywords: Ostrowski inequality, conformable fractional integral, Holder inequality, p-norm, exponential.AMS Subject Classification: 26D15, 26A33, 47A30, 33B10